Penerapan Ekstrakurikuler Qasidah Rebana dalam Penanaman Nilai Religius pada Siswa di SDN Palumbonsari 1 Karawang Timur - Muhammad Rio Gilang Ramadhan; Akil Akil; Jaenal Abidin (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
There are several ways to form religious values, including through intracurricular and extracurricular activities. In intracurricular activities, namely the cultivation of integrated religious values ​​in Islamic religious education subjects, and through extracurricular activities, one of which is participating in qasidah tambourine extracurricular activities as a form of instilling religious values, developing Islamic cultural arts, in response to the demands of the needs of students, shaping them. which is lacking, enriches the learning environment and provides stimulation for them to be more creative and of course provide learning that has been carried out in the classroom (intracurricular). The general objectives of this study were to 1) find out the application of qasidah tambourine extracurricular in inculcating religious values, 2) find out the results achieved by students in implementing qasidah tambourine extracurricular in inculcating religious values, and 3) find out the inhibiting factors in the application of qasidah tambourine extracurricular in inculcating religious values. to students at SDN Palumbonsari 1 East Karawang. The research method that the researcher uses is descriptive qualitative method, which deals with non-numerical data, collecting and analyzing narrative data. By using data collection techniques of observation, interviews, and documentation. While the data analysis researchers data reduction, data presentation, and drawing conclusions / verification. The results achieved from this research are 1) Application of qasidah tambourine extracurricular which is usually carried out once a week with an allocation of time for 3 hours of learning using training tools in the form of syllabus and assessment. In addition to the training tools, they also use a demonstration method. 2) students who take part in the qasidah tambourine extracurricular have Religious Values ​​including; have good morals, pray in congregation on time, be disciplined in prayer, and love to pray. qasidah tambourine extracurricular. 3) the inhibiting factor that affects it is in terms of time because the extracurricular implementation is only carried out once a week and some students clash with the Diniyah Takmiliyah Awaliyah (DTA) schedule, then in terms of the inadequate place in the implementation.